2015
DOI: 10.1016/j.amepre.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Vaccination in India for Children Aged 12–36 Months

Abstract: India's immunization coverage remained low in 2008, with just slightly more than half of all children aged 12-36 months fully vaccinated with UIP-recommended vaccines. A better understanding of the predictors for vaccination can help shape interventions to reduce disparities in full vaccination among children of differing demographic/cultural groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
47
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 25 publications
(44 reference statements)
10
47
3
Order By: Relevance
“…This finding accords with that of recent studies evaluating vaccine timeliness in low-and middle-income countries (LMICs), which have found significant delays in Pakistan, Nepal, and India, and begins to characterize the breadth of the problem of untimely vaccination in LMICs, leaving vulnerable children susceptible to unnecessary, preventable causes of morbidity and mortality. [23][24][25] Additionally, the data revealed that vaccinations become more untimely as the child ages progressively, indicating dropoff from the recommended schedule as the child ages, highlighting the need to maintain adherence to the schedule from birth and promote ongoing health communication regarding the importance of vaccinations for older children. Ethiopia's full vaccination coverage is persistently low, despite improving from 24.3% to 38.5% between the 2011 and 2016 DHS surveys.…”
Section: Discussionmentioning
confidence: 99%
“…This finding accords with that of recent studies evaluating vaccine timeliness in low-and middle-income countries (LMICs), which have found significant delays in Pakistan, Nepal, and India, and begins to characterize the breadth of the problem of untimely vaccination in LMICs, leaving vulnerable children susceptible to unnecessary, preventable causes of morbidity and mortality. [23][24][25] Additionally, the data revealed that vaccinations become more untimely as the child ages progressively, indicating dropoff from the recommended schedule as the child ages, highlighting the need to maintain adherence to the schedule from birth and promote ongoing health communication regarding the importance of vaccinations for older children. Ethiopia's full vaccination coverage is persistently low, despite improving from 24.3% to 38.5% between the 2011 and 2016 DHS surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is well documented that the epidemiology of nonimmunization may differ substantially from the epidemiology of partial immunization. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have focused on individual predictive factors for vaccination including gender, age, and birth order, and others on household factors such as family size, number of children below the age 3 of years, household wealth, caste, and maternal education, but most of these studies categorize vaccination status into complete (i.e., full) versus incomplete (i.e., under- or non-vaccinated). [ 13 ] Only few studies[ 11 14 ] had used three distinct vaccination categories (i.e., full-, partial, and non-vaccination) to investigate determinants of childhood vaccination in India but was limited by small sample sizes drawn from narrowly defined geographic areas potentially impacting the generalizability to the national population.…”
Section: Discussionmentioning
confidence: 99%
“…Another important consideration is how the relationship of socioeconomic status (SES) varies with vaccine hesitancy, and whether this is context-specific. Low vaccine uptake in LMICs has mostly been associated with individuals of lower SES [17][18][19][20][21], although this has been tied to disparities in access, affordability, and awareness, and less so on acceptance or hesitancy [22,23]. In contrast, more affluent individuals in high-income countries appear to be more vaccine hesitant and may have lower vaccine uptake [24][25][26].…”
Section: Introductionmentioning
confidence: 99%